Loci with genome-wide associations with schizophrenia in the Han Chinese population. (December 2015) - Li, Zhiqiang; Xiang, Yuqian; Chen, Jianhua; Li, Qiaoli; Shen, Jiawei; Liu, Yun; Li, Wenjin; Xing, Qinghe; Wang, Qingzhong; Wang, Lei; Feng, Guoyin; He, Lin; et al.
Abstract : Background: A large schizophrenia genome-wide association study (GWAS) and a subsequent extensive replication study of individuals of European ancestry identified eight new loci with genome-wide significance and suggested that the MIR137 -mediated pathway plays a role in the predisposition for schizophrenia. Aims: To validate the above findings in a Han Chinese population. Method: We analysed the single nucleotide polymorphisms (SNPs) in the newly identified schizophrenia candidate loci and predicted MIR137 target genes based on our published Han Chinese populations (BIOX) GWAS data. We then analysed 18 SNPs from the candidate regions in an independent cohort that consisted of 3585 patients with schizophrenia and 5496 controls of Han Chinese ancestry. Results: We replicated the associations of five markers ( P <0.05), including three that were located in the predicted MIR137 target genes. Two loci ( ITIH3/4 : rs2239547, P =1.17×10 –10 and CALN1 : rs2944829, P =9.97×10 –9 ) exhibited genome-wide significance in the Han Chinese population. Conclusions: The ITIH3/4 locus has been reported to be of genome-wide significance in the European population. The successful replication of this finding in a different ethnic group provides stronger evidence for the association between schizophrenia and ITIH3/4 . We detected the first genome-wide significant association of schizophrenia with CALN1, which is a predicted target of MIR137, and thus provide new evidence for the associations between MIR137 targets and schizophrenia.